Modular junction fractures in a modern rotating-platform knee arthroplasty system - Ugonna Ihekweazu, MD; P. Maxwell Courtney, MD; Elexis C. Baral, BS; Matthew S. Austin, MD; Alexander S. McLawhorn, MD, MBA (Arthroplasty Today, 2019)
In this series, we report the findings from four patients who presented with pain and mechanical symptoms after revision total knee arthroplasty with the DePuy Sigma TC3 RP prosthesis. Plain radiographs for each patient demonstrated failure of the femoral component at the modular junction of the femoral prosthesis. Retrieved implants at the time of surgery revealed fractures occurring exclusively at the femoral adapter bolt and the corresponding adapter. Retrieval analysis was performed on two of the four cases by visual light microscopy. Our findings suggest that the implants had suffered from fatigue fractures likely due to cyclic loading. This is the first case series to describe the failure mechanism and clinical scenarios contributing to failure of the femoral locking bolt and adapter sleeve in this prosthesis. Keywords: Total knee arthroplasty, Implant failure revision, Modular